A Latent Profile Analysis of Online Dating Patterns Among Single Young Men Who Have Sex with Men. - Choi, Seul Ki; Bauermeister, José (AIDS & Behavior, 2022)
Despite the increased use of geosocial networking applications for finding sexual partners among young men who have sex with men (YMSM), few studies have examined the intricate patterns of online dating behaviors. In order to advance understanding of online dating patterns among YMSM, various factors, including how frequently and how much time is spent within partner-seeking sites, need to be examined concurrently. Therefore, we used latent profile analysis to identify online dating patterns and logistic regressions to examine their associations with sexual behaviors and relationship characteristics among single YMSM (N = 180; ages 18–24). We found three online dating patterns: discouraged users (N = 93, 52%), date seekers (N = 67, 37%), and instant lovers (N = 20, 11%). Discouraged users were less likely to seek sexual sensational activities, while date seekers were more likely to seek sexual sensational activities. Moreover, instant lovers were less likely to pursue committed romantic relationships, while they reported a higher number of condomless anal intercourse. Given that online dating patterns are not homogeneous, HIV prevention interventions may benefit from tailored approaches based on YMSM's different online dating profiles.